The understanding, application and influence of complexity in national physical activity policy-making - Benjamin P. Rigby; Caroline J. Dodd-Reynolds; Emily J. Oliver (BMC, 2022)
Abstract Background Complexity theory and systems-thinking are increasingly popular in physical activity (PA) research and policy discourse. The impact of this perspective shift, across many sectors, may be underwhelming. We explore why, by focusing on how these concepts are understood and applied by PA policy-makers. This is of particular interest given the challenges of multisectoral interest and poorly defined stakeholder boundaries that are associated with PA promotion. In this study, we critique key elements of complexity theory and consider how it is understood and put into practice in PA policy-making. Methods We adopted a complex realist position. Ten semi-structured interviews were conducted with national-level policy-makers from United Kingdom government settings (five civil servants, three politicians, two policy advisors). An inductive thematic analysis was conducted, and managed with NVivo 10 software. Results Three overarching themes were constructed to reflect policy-makers' uncertainty about complexity and the application of such perspectives to this policy space, their sense that PA was an unexceptionable yet unclaimed policy issue, and their desire for influence and change. Participants discussed complexity in contrasting ways. Its meaning was context-dependent and dynamic, which generated uncertainty about applying the concept. Participants also perceived an increasingly diverse but ill-defined PA policy system that spans the domains of expertise and responsibility. Collaborative practices may contribute to a previously unobserved sense of detachment from the systems' complexity. Nevertheless, participants suggested potentially effective ways to stimulate system change, which require passionate and enterprising leadership, and included varied evidence use, a focus on localised implementation and different ways to connect people. Conclusions This research highlighted the importance of extending complexity theory and systems-thinking. While emphasizing the prevalence of these ideas across the PA sector, there is uncertainty as to their meaning and implications. This may prevent their use in ways that enhance PA policies and programmes. Participants conceptualised PA as a tool, which was imposed on the system. While this may support participative decision-making and localised implementation, further research is needed to understand how local systems foster leadership, the practical application of complexity and systems-thinking, and how to support system-wide change in the development and implementation of PA policies.